The Lower Jurassic Posidonia Shale in the Swabian Alb Geopark – Geoeducation in an Industrial Environment - Annette Schmid-Röhl (Geoconservation Research)
The Lower Jurassic Posidonia Shale of Southern Germany is famous for its excellently preserved fossils. First of all, the large and spectacular ichthyosaurs, pterosaurs and crocodiles impress. Fish, crinoids, ammonites and belemnites are witnesses of a very special living world in the former Posidonia Shale Sea. The rather small and inconspicuous bivalves, brachiopods and serpulids provide important clues about conditions in the ecosystem. The Posidonia Shale is one of the best-known fossil deposits in the world, and for centuries has provided scientists with an enormous wealth of information. One of the most important fossil collections is displayed in the Fossil Museum of the Werkforum in Dotternhausen. Together with the quarries (active and recultivated), the museum offers unique opportunities for scientific and geoeducational purposes.